Strategi Gereja Katolik dalam Upaya Meningkatkan Partisipasi Politik di Keuskupan Agung Semarang - Alfonsus Ega Putria Warsanto; Fitriyah - - (Journal of Politic and Government Studies, 2020)
Religion has a great influence on social life, including in politics. Islam, the majority religion in Indonesia, has long participated in politics, both through social organizations and political parties. Meanwhile, other religions have their views about politics, including Catholicism. The Catholic Church, as an institution of the Catholic Religion, has issued various official documents on politics, both at the world level and at various levels below, such as the Archdiocese of Semarang. These documents show that the Archdiocese of Semarang is trying to increase the political participation of its people. This research uses a qualitative method by conducting interviews with speakers, observations, and study of official documents of the Catholic Church. Political theory, political participation, and strategy are used to analyze findings in research. After conducting research, several obstacles were found, namely the lack of understanding of the political community, feeling as a minority, and the political situation that was not conducive, due to the emergence of primordial groups that gave rise to sectarian politics. The Catholic Church has a strategy, which consists of internal and external strategies. Internal strategy, targeting people and priests aims to instill understanding and knowledge of Catholic views, attitudes, and values in politics and prepare people for political contestation. Meanwhile, an external strategy in the form of cooperation with the KPU, Bawaslu, social organizations, and political parties, one of the aims is to create a conducive political climate for all groups. The researchers found that there were inhibiting factors in the church hierarchy, at the parish level, when there were lay people who had personal political interests so that the church's strategy did not reach everyone, especially those who fought in elections. Also, strategies to prepare people to participate in contestation are considered too short, only when a political year.